1995
DOI: 10.1063/1.469685
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of the reaction pathway for methane activation on a gallium site in metal exchanged ZSM-5

Abstract: Density functional theory is used to describe the reaction profile for methane dissociation on Ga-exchanged ZSM-5. Stable structures on the reaction pathway are characterized as weakly adsorbed methane molecule and the C-H dissociation product. The transition state is also explicitly defined and optimized. The nonlocal density functional approximation is invoked to calculate the energy parameters of the reaction. The activation barrier is estimated at about 120 kJ/mol, in excellent agreement with other similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 36 publications
5
35
1
Order By: Relevance
“…To this end, we have calculated various reaction steps over neutral HGa(OH) 2 moieties (equations (16) and (17)) which are very similar to equations (7) and (8).…”
Section: Z(h)agaah(d)(od)¡z(h)agaad(o) þ Hd ð15þmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have calculated various reaction steps over neutral HGa(OH) 2 moieties (equations (16) and (17)) which are very similar to equations (7) and (8).…”
Section: Z(h)agaah(d)(od)¡z(h)agaad(o) þ Hd ð15þmentioning
confidence: 99%
“…[15][16][17], we chose a 1-T(UC) zeolite cluster model (figure 1), because it presents a simple and practical approximation of cation position structure, formed by a lattice aluminium ion. Comparative calculations for 1-T(UC) and 5-T(UC) clusters [15] have shown that the results obtained using these clusters are rather similar.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The role of gallium in the aromatization reaction has been investigated by numerous experimental [7][8][9][10][11][12][13] and theoretical [14][15][16][17][18][19][20][21] studies. Many authors agree that the aromatization reaction occurs via a bifunctional mechanism, and gallium enhances the dehydrogenation steps including the dehydrogenation of alkane, higher olefins and cycloolefins [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The water-induced enhancement in the rate of alkane activation by Ga/ZSM-5, as discussed herein, relates to transformation of these single Ga + centers to binuclear cationic Ga complexes involving a Ga 2 O 2 2+ core. Recent experimental [5][6][7][8] and computational [9][10][11][12][13] studies have contributed to our understanding of the mechanism of alkane activation by single Ga Lewis acid sites. As candidate active sites, various mononuclear Ga-containing cations (Ga…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Quantumchemical calculations [13] showed that CÀH bond activation by reduced Ga/ZSM-5 proceeds over the Lewis acid-base pair formed by the Ga + ion and a zeolite-framework basic oxygen anion (Ga + ···ZO À ). The experimentally observed increase in activity of Ga + species in ZSM-5 upon oxidation at 473 K by nitrous oxide was ascribed to formation of gallyl (GaO + ) ions.…”
mentioning
confidence: 99%